Indigenous knowledge: examining its past and present status, and projecting its future in library and information services (2006)
Indigenous knowledge systems is a growing area of research in the information age. Over six million, one hundred and sixty thousand records exist on the subject. In spite of this, Indigenous Knowledge(IK) is still far from being preserved for posterity. The paper examines the history of IKS, treats classification of IKS in library classification schemes and projects the future of IKS. The efforts at indigenous knowledge gathering in the University of Ibadan, at the Department of Library , Archival and Information Studies and the Institutes of African Studies are reported. Recommendations are that information professionals should evolve systems for organizing oral information, policies should be made to encourage the recording, documentation of IK, and national, regional and if possible, global networks can be created to facilitate this.